Erratum: YOUNG-HYO KIM, ED A. HENDRYCKS & KYUNG-SOOK LEE (2011) The genus Guernea Chevreux, 1887 from Korean waters (Crustacea: Amphipoda: Dexaminidae) Zootaxa, 3104, 1–25. - Kim, Young-Hyo; Hendrycks, Ed A.; Lee, Kyung-Sook (Zootaxa, 2011)
(Erratum)